2006
DOI: 10.1073/pnas.0601903103
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of isolated DNA molecules: Dependence on length and topology

Abstract: The conformation and dynamics of circular polymers is a subject of considerable theoretical and experimental interest. DNA is an important example because it occurs naturally in different topological states, including linear, relaxed circular, and supercoiled circular forms. A fundamental question is how the diffusion coefficients of isolated polymers scale with molecular length and how they vary for different topologies. Here, diffusion coefficients D for relaxed circular, supercoiled, and linear DNA molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

38
322
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(364 citation statements)
references
References 54 publications
38
322
4
Order By: Relevance
“…The values of solute diffusivity considered here are in the order of 10 À11 -10 À14 m 2 /s, which is typical for high molecular weight proteins and DNA. 52 This results in the Schmidt number in the order of 10 5 -10 8 . Since, mass transfer boundary layer thickness is inversely proportional to Schmidt number, it may be considered that thickness of mass transfer boundary layer would not more than 0.1-0.2% of the tube radius (typical microtube diameter are in the range of 50-500lm).…”
Section: -3mentioning
confidence: 99%
“…The values of solute diffusivity considered here are in the order of 10 À11 -10 À14 m 2 /s, which is typical for high molecular weight proteins and DNA. 52 This results in the Schmidt number in the order of 10 5 -10 8 . Since, mass transfer boundary layer thickness is inversely proportional to Schmidt number, it may be considered that thickness of mass transfer boundary layer would not more than 0.1-0.2% of the tube radius (typical microtube diameter are in the range of 50-500lm).…”
Section: -3mentioning
confidence: 99%
“…properties of ring polymers in the ring-linear blends. [24][25][26][27][28][29][30][31] Iyer et al 28 proposed a scaling model on the size of ring polymers in ring-linear blend and found that by gradually increasing the composition of linear chains, the ring molecules swell, with Flory's scaling exponent v increasing from 0.4 to 0.5 in the limit of infinite dilution for the rings. Using the BFM, Subramanian and Shanbhag 29,30 studied the dynamics of entangled ring polymers in ring-linear blends and found the self-diffusion coefficient and the primitive path length of ring polymers are more sensitive to volume fraction than that of linear chains.…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with the results of Robertson et al on DNA. [25][26][27] By tracking the Brownian motion of individual tracer DNA molecules in blend of four topological combinations, Robertson et al found that the molecular topology, especially for the case of circular DNA molecules surrounded by linear molecules, have a strong effect on the diffusion at above certain concentration or molecular weight. Their findings suggest that free ends play a critical role in generating entanglements which retard diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Thus we show further that spatially confined molecules fold into specific conformations close to those found for linear chains, and strongly dependent on the size of the confining box. DOI: 10.1103/PhysRevLett.106.248301 PACS numbers: 82.35.Gh, 87.64.Dz, 36.20.Ey, 87.14.gk Ring closure of a polymer is one of the important factors influencing its statistical mechanical properties [1], e.g., scaling [2,3], shape [4,5], and diffusion [6][7][8], because it restrains the accessible phase space. The theoretical description of circular chains (knots or catenanes) is a challenging problem, owing to the difficulties inherent to a systematic theoretical analysis of such objects constrained to a unique topology.…”
mentioning
confidence: 99%
“…Ring closure of a polymer is one of the important factors influencing its statistical mechanical properties [1], e.g., scaling [2,3], shape [4,5], and diffusion [6][7][8], because it restrains the accessible phase space. The theoretical description of circular chains (knots or catenanes) is a challenging problem, owing to the difficulties inherent to a systematic theoretical analysis of such objects constrained to a unique topology.…”
mentioning
confidence: 99%